Choice Not Chance - McCallie, Joanne P., 1965-; Rains, Rob (Tantor Media, Inc., 2020)
Coach P created the Choice Not Chance philosophy which focuses on making the correct choices in life. The philosophy is widely used by McCallie, her staff and players, who are very active in the community speaking about "CNC." Age 26 when she took over at Maine, Coach McCallie was the youngest head coach in Division I history. She took that program from nothing and built it into a very competitive team in a span of eight years. She started to outdraw the men's team, a rarity in college sports. Maine went from drawing 800 fans a game to 5,800, a sellout crowd. McCallie put her heart and soul into Maine, which she says you must do in any job if you truly want to be successful. She learned to fight for the things she thought were important for her program, and she did not want to accept the status quo. She didn't want women's sports to be treated like an ugly stepdaughter. This is the philosophy she imparts to all of her players and now brings to her efforts as head coach of a true national powerhouse at Duke. Drawing on Coach McCallie's experiences at Maine and Duke and throughout her career, Choice Not Chance highlights lessons for building a fierce competitor, such as "Going against the grain" and "Never become satisfied."